A rare case of a pericardial mass: Myelosarcoma from relapsed acute monoblastic leukaemia without bone marrow involvement. Issue 4 (25th October 2017) - Binny, Simon; Tomlinson, Stephen; Hammett, Christopher; Dahiya, Arun; Pillai, Elango; Prasad, Sandhir B.
Abstract: Introduction: A 67‐year‐old male presented with progressive exertional dyspnoea, night sweats and 25 kg of weight loss over 2 years. He was febrile, 38.0°C, hypotensive and tachycardiac. Pulsus paradoxus was present. His electrocardiogram showed electrical alternans. He had previously had acute myeloid leukaemia treated with three cycles of chemotherapy. Results: The patient was found to have a 3.6 cm pericardial effusion with features consistent with tamponade and three cardiac masses (largest 10 × 9 × 5 cm) and mediastinal lymphadenopathy. He had 825 mL of pericardial fluid drained from which cytology was consistent with extramedullary leukaemia. A bone marrow aspirate and trephine was normal. Conclusion: The findings suggested extramedullary recurrence of leukaemia in the pericardium, without bone marrow involvement.